Radio-Iodination Methods for the Production of SPECT Imaging Agents - Wager, K. M.; Jones, G. B. (Current Radiopharmaceuticals, 2010)
Molecular imaging via Single Photon Emission Computed Tomography (SPECT) holds considerable promise for analysis of metabolism and bio-distribution of drugs in addition to imaging of diseased states. While the related Positron Emission Tomography (PET) imaging offers higher resolution images, SPECT is considered the more practical approach to nuclear imaging for routine diagnostic use. One of the attractive features of SPECT is its utilization of medium to long-lived radioisotopes, particularly radio-iodinated species. This mini-review will survey recent advances in radioiodination, including synthetic chemistry and post-labeling purification methods.
Keywords: halodethallation